The Core Competencies in the Digital Age for Teachers in Schools under the Roi Et Primary Educational Service Area Office 2 - Chantakam, Emorn; Phrakhruvijitpanyaporn (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2021)
The objective of the research article were 1) to study the core competencies in the digital age for Teachers in Schools, 2) to compare the core competencies in the digital age for teachers in schools, 3) to study guideline for the development of the core competencies in the digital age for teachers in schools under the Roi Et Primary Educational Service Area Office 2. The samples used in this research were 351 teachers schools under the Roi Et Primary Educational Service Area Office 2. The tools used were a questionnaire and the semi-structured interview form. The statistical structures used in quantitative research are frequency, percentage, mean, standard deviation. The statistics used for the hypothesis examination were t-test and F-test. The qualitative data analysis was descriptive writing. The result of this research found that: 1. the core competencies in the digital age for teachers in schools overall was at a high level, ranked from the areas with high averages to the low : teamwork, good service, self-development, focusing on the achievement in performance, ethical, and code of ethics of teaching profession. 2. Result of comparison the core competencies in the Digital Age for Teachers in Schools, classified by gender, educational level, and work experience overall and aspects, the difference was statistically significant at the .05 level. 3. Result of guideline for the development of the core competencies in the digital age for teachers in schools : have perseverance and work hard, serving with smile, friendly, willing to welcome and make impression, has the ability to lead himself, able to develop themselves according to their actual conditions, have unity with the team, build and sustain society in the desired direction.